Meigs’ syndrome in a young patient: A case report - Ha, Pham Hoang; Thai, Pham Quang; My, Nguyen Tra; Vong, Me Quoc; Hieu, Tong Quang (Tạp chí Nghiên cứu Y học, 2026)
Meigs syndrome is a rare benign condition defined by the triad of a benign ovarian tumor, ascites, and pleural effusion, which resolve after tumor removal. It commonly occurs in postmenopausal women and may mimic malignancy due to elevated CA-125 levels and fluid accumulation. It is extremely rare in females under 30. A 17-year-old girl presented with a palpable lower abdominal mass, without fever or weight loss. CT scan revealed a 110×70 mm pelvic mass, ascites (53 mm), bilateral pleural effusion, and elevated CA-125 (340.8 U/mL). Exploratory surgery and frozen section biopsy confirmed a benign ovarian fibroma. Only the affected adnexa were removed, preserving reproductive organs. Symptoms resolved completely after surgery. Meigs syndrome should be considered even in young patients with ovarian masses and effusions. Timely surgery with intraoperative frozen section is crucial for diagnosis and fertility-preserving treatment.